IUTAM A Short History - Eberhard, Peter; Juhasz, Stephen (Springer International Publishing : Imprint: Springer, 2016)
This book presents extensive information related to the history of IUTAM. The initial chapters focus on IUTAM's history and selected organizational aspects. Subsequent chapters provide extensive data and statistics, while the closing section showcases photos from all periods of the Union's history. The history of IUTAM, the International Union on Theoretical and Applied Mechanics, began at a conference in 1922 in Innsbruck, Austria, where von Kármán put forward the idea of an international congress including the whole domain of applied mechanics. In 1946 IUTAM was then formally launched in Paris/France. IUTAM has since time organized more than 24 world congresses and 380 symposia, representing all fields of mechanics and highlighting advances by prominent international researchers. The efforts of IUTAM and its about 50 member countries serve to promote the mechanical sciences and the advancement of human society, addressing many key challenges. In this context, IUTAM preserves important traditions while at the same time recognizing new challenges and adapting its structures and processes accordingly. The first edition of this book was published in 1988. This new book now offers an updated and completely revised edition reflecting the substantial developments in the interim.